Extension features for Magento - Liang, Xiuhui. (2012)
Electronic Commerce (E-commerce) and was a viable proposition for IT developer to work on. But solutions are simply obtainable in the market. To continue progress in this domain, a more suitable approach was to select a solution and developed extension features to refine its solution.